2013
DOI: 10.1002/sim.6061
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of glaucoma data

Abstract: We refer glaucoma to a category of eye disorders often associated with a dangerous buildup of intraocular pressure (IOP), which can damage the eyes' optic nerve that transmits visual information to the brain. Because IOP changes over time, it is a function of time, and it is an advantage that we analyze the phenomenon using functional data analysis. In this paper, we treat the data related to the IOP of 35 patients with right eye glaucoma, collected in Rasul-e-Akram Hospital at Tehran, Iran, over the years 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…In the present study, total variation was explained ≥90% for height and weight respectively. In literature review, application of FPC analysis are reported more than 80% of the total variation in multiple studies [ 9 , 34 , 38 , 39 ]. In fact, we know that the growth outcome measurement obtained every month for 3 years exhibits 40% of the children had poor growth in the slum area, Vellore.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, total variation was explained ≥90% for height and weight respectively. In literature review, application of FPC analysis are reported more than 80% of the total variation in multiple studies [ 9 , 34 , 38 , 39 ]. In fact, we know that the growth outcome measurement obtained every month for 3 years exhibits 40% of the children had poor growth in the slum area, Vellore.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, total variation was explained ≥ 90% for height and weight respectively. In literature review, application of FPC analysis are reported more than 80% of the total variation in multiple studies [25,29,31,32].…”
Section: Discussionmentioning
confidence: 99%
“…The advanced statistical procedure of Functional Principal Component Analysis was used to extract the information from functional data to identify the different pattern of the child growth function and further functional linear model was used to assess the association between factors and trajectories [13,15,16,18,[23][24][25][26][27]. The statistical analysis was performed using R studio version 3.6.1.…”
Section: Smoothing Outlying Function and Fpcamentioning
confidence: 99%
“…This was in part due to the known clinical utility of some clinical parameters for the diagnosis of glaucoma, compared with others that are comparatively low yield. The principal components in this study represent clinical variables that may be correlated in their contributions for explaining differences between high‐ and low‐tension glaucoma 23,36–38 …”
Section: Methodsmentioning
confidence: 99%